HUBUNGAN RELIGIUSITAS, OPTIMISM, SOCIAL SUPPORT, DAN PSYCHOLOGICAL WELL-BEING PESERTA DIDIK MAN SE-KOTA MALANG - Muhammad Farid Ilhamuddin; Muslihati Muslihati; Dany Moenindyah Handarini (Pascasarjana Universitas Negeri Malang, 2017)
This study aims to know the relation between religiousity (X1) and psychological well being (Y), the relation between optimism (X2) and psychological well being (Y), as well as the relation between social support (X3) and psychological well being (Y) of students of MAN in the entire Malang city. This study was a non-experimental study with causal relationship study plan. The result of this research showed that there was a positive significant between X1 and Y, X2 and Y, X3 and Y; X1, X2, X3 had strong linear relation with Y; the influence of the three independent     logical well being (Y), optimism (X2) dan psychological well being (Y), social support (X3) and psychological well being (Y) student of MAN se-Kota Malang. Penelitian ini bertujuan untuk mengetahui hubungan religiusitas (X1) dan psychological well being (Y), optimis (X2) dan psychological well being (Y), social support (X3) dan psychological well being (Y) peserta didik MAN se-kota Malang. Pendekatan yang digunakan adalah non experimental research dengan jenis penelitian causal relationship study. Hasil penelitian menunjukkan ada hubungan positif signifikan antara X1 dan Y, X2 dan Y, X3 dan Y; X1, X2, X3 memiliki hubungan linear yang kuat dengan Y; pengaruh ketiga variabel independen psychological well being (Y), optimism (X2) dan psychological well being (Y), social support (X3) dan psychological well being (Y) peserta didik MAN se-Kota Malang.